Linear Hashing - Alon, Noga; Dietzfelbinger, Martin; Miltersen, Peter Bro; Petrank, Erez; Tardos, Gábor (BRICS Report Series, 1997)
Consider the set H of all linear (or affine) transformations between two vector spaces over a finite field F. We study how good H is as a class of hash functions, namely we consider hashing a set S of size n into a range having the same cardinality n by a randomly chosen function from H and look at the expected size of the largest hash bucket. H is a universal class of hash functions for any finite field, but with respect to our measure different fields behave differently.